2022
DOI: 10.1016/j.cmi.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing for surveillance of tuberculosis drug resistance and determination of resistance level in China

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…29 This breakpoint artifact has been also observed in a study in China which used quantitative Sensititre MYCOTB plates. 30 Also, different mutations in gyrB at amino acid positions 499-501 (the quinolone binding pocket) exhibit variable effects on the resistance level to different fluoroquinolones, in line with a previous study. 31 We also confirmed results of other studies suggesting that the gyrB Glu501Asp mutation confers resistance to moxifloxacin but not to levofloxacin at the currently endorsed critical concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…29 This breakpoint artifact has been also observed in a study in China which used quantitative Sensititre MYCOTB plates. 30 Also, different mutations in gyrB at amino acid positions 499-501 (the quinolone binding pocket) exhibit variable effects on the resistance level to different fluoroquinolones, in line with a previous study. 31 We also confirmed results of other studies suggesting that the gyrB Glu501Asp mutation confers resistance to moxifloxacin but not to levofloxacin at the currently endorsed critical concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the proportion of borderline rpoB mutations in rifampicin-resistant Mycobacterium tuberculosis isolates, ranging from 3.3% to 13.1%. 3 , 10–12 The reported proportion of 20.4% in china 7 is higher than other countries. This study provided evidence that only 43.9% of rifampicin resistance conferred by borderline mutation was detected by L-J medium-based DST at the critical concentration of 40.0μg/mL 6 with 4-week incubation.…”
Section: Discussionmentioning
confidence: 88%
“…In china, borderline rpoB mutations accounted for 20.4% of the total rpoB mutations detected. 7 Regarding the higher prevalence of borderline rpoB mutations and commonly used phenotypic DSTs in China, the ability of L-J medium-based DST to detect borderline rifampicin resistance conferred by specific mutations was explored in comparison with molecular based Xpert MTB/RIF.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, we collected sputum from patients on a continuous basis and performed pictures and cultures, which explained the low bacteriological examination. This is a common problem in most tuberculosis outbreak investigations, which has limited our understanding of the whole transmission network ( 30 ). Second, we did not follow those students who received preventive therapy for a long enough time.…”
Section: Discussionmentioning
confidence: 99%